2006
DOI: 10.1080/16501970600694859
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic and Kinetic Asymmetries in Hemiplegic Patients’ Gait Initiation Patterns

Abstract: Quantitative data obtained on the gait initiation phase suggest that hemiplegic patients develop asymmetrical adaptive posturo-motor strategies to compensate for their impairments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
63
2
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(73 citation statements)
references
References 17 publications
3
63
2
5
Order By: Relevance
“…However, few studies have demonstrated how GRFs are affected in the anteroposterior axis during GI after stroke (Tokuno and Eng, 2006;Brunt et al, 1995;Bensoussan et al, 2006). Further, only one of these studies has demonstrated how GRFs are affected in the mediolateral axis (Brunt et al, 1995).…”
Section: Introductionmentioning
confidence: 95%
“…However, few studies have demonstrated how GRFs are affected in the anteroposterior axis during GI after stroke (Tokuno and Eng, 2006;Brunt et al, 1995;Bensoussan et al, 2006). Further, only one of these studies has demonstrated how GRFs are affected in the mediolateral axis (Brunt et al, 1995).…”
Section: Introductionmentioning
confidence: 95%
“…Using kinematics, foot drop was determined by measuring toe elevation ( Fig. 3a; Bensoussan et al, 2006;Chin et al, 2009;Weber et al, 2004). This measure was correlated with overground speed, the patients having the lowest toe elevation taking a longer time to walk 10 m (Fig.…”
Section: Locomotor Training Induces Cortical Plasticity After a Lesiomentioning
confidence: 99%
“…Maximum toe elevation has been used previously [17][18][19] and is a simple measurement for culling out the effect of CST lesion on gait function. It clearly reflected CST impairment, although compensations used by the participants to overcome foot drop were probably not completely excluded from those measurements.…”
Section: Foot-drop Measurementsmentioning
confidence: 99%